Intravenous administration of human Muse cells recovers blood flow in a mouse model of hindlimb ischemia - Hori, Yusuke; Kitani, Tomoya; Yanishi, Kenji; Suga, Takaomi; Kogure, Masaya; Kusaba, Tetsuro; Kushida, Yoshihiro; Dezawa, Mari; Matoba, Satoaki (Frontiers in Cardiovascular Medicine, 2022)
Cell-based therapies hold great promise for the treatment of peripheral arterial disease (PAD), especially in patients with limb-threatening ischemia, although the optimal strategy remains to be explored. In this study, we evaluated the therapeutic effect of intravenous administration of human Muse cells, a unique subpopulation of mesenchymal stem cells (MSC), using a mouse model of hindlimb ischemia (HLI) without an immunosuppressant. Compared with the PBS or non-Muse MSC groups, the Muse group showed significantly higher laser doppler blood flow in the ischemic limb at days 7 and 14 after HLI. Increased microvascular density (percent area of CD31(+) cells) and reduced interstitial fibrosis in the ischemic limb muscle were also observed in the Muse group. mCherry-expressing Muse cells were found in the ischemic border zone and expressed CD31 but did not in the non-ischemic limb. Muse cells produced higher amounts of vascular endothelial growth factor (VEGF) than non-Muse cells under normoxic and hypoxic conditions in vitro. In the ischemic muscle, tissue VEGF concentration and angiogenesis-related genes such as Vegfa, Angpt1, Pdgfb, and Igf1 were significantly higher in the Muse group than in the other groups. In addition, the proportion of M2 macrophages to total macrophages and the ratio of anti-inflammatory-related genes such as IL-10, Arg1, and CD206 per iNOS were significantly higher in the Muse group than in the other groups. In summary, Muse cells exert pleiotropic effects in a mouse model of HLI, and therefore may provide a novel therapeutic approach for the treatment of PAD patients with limb-threatening ischemia.